We have to find the derivative of f(x) = 5x * (x-1)^4

We can use the product rule here:

f(x) = 5x * (x-1)^4

f'(x) = (5x)' * (x-1)^4 + 5x * [(x-1)^4]'

=> f'(x) = 5* ( x - 1)^4 + 5x * 4*(x - 1)^3

=> f'(x) =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find the derivative of f(x) = 5x * (x-1)^4

We can use the product rule here:

f(x) = 5x * (x-1)^4

f'(x) = (5x)' * (x-1)^4 + 5x * [(x-1)^4]'

=> f'(x) = 5* ( x - 1)^4 + 5x * 4*(x - 1)^3

=> f'(x) = 5(x - 1)^4 + 20x(x - 1)^3

**The required derivative is f'(x) = 5*(x - 1)^4 + 20*x*(x - 1)^3**